Problems of Forming the Digital Competence of the Staff of Methodological Services in the System of In-Service Teacher Training Education - Solohub, Oleksandra (Pedagogical Discourse, 2017)
In this article, the author raises the problem of digital transformation as one of the world trends. The article deals with one of the key competences of a modern citizen - digital competence. The author analyzes the contemporary scientific literature for defining digital competence, as well as the content of digital competence provided by scientists from different countries, in accordance with the recommendations of the European Parliament and the Council of Europe of 18 December 2006, on key competences for lifelong learning. The author focuses on the documents of the European Commission’s science and knowledge service on the Digital Competency Framework (DigComp); UNESCO materials that prove the importance of integrating digital literacy with other core competencies in students’ professional and private life for the development of 21st century skills; Canada’s centre for digital and media literacy, which refers to digital literacy as «The Multi-Literacies of the Digital Age» and illustrates digital literacy as a wide range of interrelated skills that traditionally fall under media literacy, technology literacy, information literacy, visual literacy, communication literacy and social literacies. The author also raises the problem of the digital gap between pupils and teachers, urban and rural citizens, and the problem of the digital competence of methodological service workers. Great attention has been paid to the analyses of the literature on models of methodological work, professional competence of a methodologist, preparation of pedagogical workers to use information and communication technologies in education. Special attention is paid to the problem of the formation of professional competence of workers of the united territorial communities, which are now actively being created in Ukraine. The author has analysed the world practice aimed at the essence and content of digital competency and the formation of digital competence of teachers (DigCompEdu). The components of the model of digital competence of teachers of Norway are presented. Estonia is one of the leading European countries in terms of digital literacy. The author gives an example of the implementation of the strategy of continuous education in Estonia, and the activity of the Ministry of Education and Science of Estonia in implementing this strategy. The article proves the necessity of creating a model of organizational and pedagogical conditions for the formation of digital competence of a methodologist of district, city, united territorial community.